Racial Bias Within The Blue Vein Society in The Blacker The Berry by Wallace Thurman - Latroch, Ikram (My University, 2020)
The aim of this research is to dive into the issue of colorism and attempt to get to its depths including the effect this phenomenon has on the African-American society as a whole and on individuals. The paradox is explored through the eyes of Wallace Thurman in his novel The Blacker The Berry (1929) , the exposition of such delicate topic aims to emphasize that hate isn’t only interracially but intraracially as well, taking into consideration the event of black history or rather the African-American fight to win freedom , that would eventually be brushed off by aristocratic white thoughts implanted in the light skinned minds . In the novel, the blue vein society is that portion affected by white supremacy in which the protagonist, born with a very dark complexion struggles for most of her life with unending rejection from those around her. Subjected to such treatment, she wishes to be different in order to fit in, in a society where she would belong naturally, one had to struggle and pave her way to self-love and acceptance, that is what one would eventually conclude as a reward for the hardships endured. The research will answer many interrogations starting with: how did colorism begin? how does colorism affect people? and how is one defined by their skin color?
Keywords: Colorism; Blackness; Race and Racism; Blue vein society; Identity; Hate; Discrimination; Acceptance; Self-esteem